New frontiers of legal translation: blogs by and for translators - Pontrandolfo, Gianluca (Estudios de Traducción, 2020)
The present study reflects upon a specific category of legal translation tools, i.e. blogs by and for legal translators, from a double perspective. From a theoretical perspective, the research focuses on some key notions of Translation Studies (translation unit, problem, error, method, strategy, technique and equivalence) and how they change in these virtual environments. On the other hand, it explores the co-construction and sharing dynamics in action in the posts written by and for communities of legal translators.The paper presents paradigmatic examples of some of the most followed blogs of legal translators (especially in the Spanish-English combination), focusing on a specific case study:  the blog of Rebecca Jowers. The analysis is carried out through a prism of different perspectives, exploring concepts from different methodological angles (documentation in legal translation, specialised lexicography, popularisation and mediation of law, marketing and the sociology of professions).
Keywords: legal translators’ blogs; legal translation tools and resources; translation networks; Translation Studies; Rebecca Jowers